The neural correlates of ideation in product design engineering practitioners. (2019) - Hay, L.; Duffy, A. H. B.; Gilbert, S. J.; Lyall, L.; Campbell, G.; Coyle, D.; Grealy, M. A.
Abstract : In product design engineering (PDE), ideation involves the generation of technical behaviours and physical structures to address specific functional requirements. This differs from generic creative ideation tasks, which emphasise functional and technical considerations less. To advance knowledge about the neural basis of PDE ideation, we present the first fMRI study on professional product design engineers practising in industry. We aimed to explore brain activation during ideation, and compare activation in open-ended and constrained tasks. Imagery manipulation tasks were contrasted with ideation tasks in a sample of 29 PDE professionals. The key findings were: (1) PDE ideation is associated with greater activity in left cingulate gyrus; (2) there were no significant differences between open-ended and constrained tasks; and (3) a preliminary association with activity in the right superior temporal gyrus was also observed. The results are consistent with existing fMRI work on generic creative ideation, suggesting that PDE ideation may share a number of similarities at the neural level. Future work includes: functional connectivity analysis of open-ended and constrained ideation to further investigate potential differences; investigating the effects of aspects of design expertise/training on processing; and the use of novelty measures directly linked to the designer's internal processing in fMRI analysis.